The Impact of Masturah Program on The Families of Tablighi Jamaat at Temboro Village in Indonesia - Zainal Arifin; Bulbul Ashraf Siddiqi; Dudung Hamdun; Sri Rahmi (Nazhruna: Jurnal Pendidikan Islam, 2021)
Islam sets the roles and relationship between husband and wife in the family in a balanced manner to create sakinah, mawadah, and rahmah (peaceful, loving, and compassionate) family. A lot of people often underestimate the role of a wife in a family. This paper examined the Masturah (rather than putting Arabic words, it would be better to write the meaning of the Masturah) as the education program for wife in the family of Tablighi Jamaat in Temboro village, Magetan, East Java, Indonesia. This research used a qualitative approach where the data were collected, applying interviews with various family members of the Tablighi Jamaat. The research results show that the Masturah is a closed and private education strategy for a wife (the Masturah) in the families of Tablighi Jamaat, which is performed in the house with religious training and practice. Second, the purpose of the Masturah is to prepare the role of wife as mu’allimah and muta’alimah, daiyah, and a’bidah (teacher and student, preacher, and worshiper). Third, the Masturah helps to increase Iman (the belief in Allah (the practice in worship, appreciation in practicing Islamic religion, improving the knowledge in Islamic teaching, and the increase of motivation in religion and preaching. This research has implications for the importance of religious education for wives to support their husbands' da'wah activities and children's education at home.